Does the mixing method of AH Plus Jet affect its physicochemical and mechanical properties? - Rosa, Stefani Jovedi (2024)
The aim of this study was to evaluate the influence of auto mix and manual mixing on the physicochemical and mechanical properties of AH Plus Jet sealer (Dentsply/DeTrey). Evaluated properties included radiopacity, initial and final setting times, flow, and solubility, following the specifications outlined in ISO 6876/2012 and ADA No. 57/2000. pH levels were measured at intervals of 3, 24, 72, and 168 hours. Push-out bond strength testing was performed using a universal testing machine (Instron, Canton, MA, USA), and failure modes were analyzed with stereomicroscopy (Stemi 508; ZEISS). One-way analysis of variance and Tukey tests, unpaired Student\'s t-tests, or Mann-Whitney tests were used with a significance level of 5%. Regarding radiopacity, the auto mix method presented a radiopacity value of 12.11 mmAl, while manual mixing showed 12.55 mmAl (P>0.05). For initial and final setting times, auto mix showed 901 minutes and 1779 minutes, respectively, while manual mixing recorded values of 631 minutes and 1504 minutes (P<0.05). In terms of flow, auto mix demonstrated higher values (25.26 mm) than manual mixing (21.71 mm) (P<0.05). No statistical differences were observed between the two methods for solubility and pH (P>0.05). Finally, manual mixing showed a higher bond strength value (14.52 MPa) compared to auto mix (9.81 MPa) (P<0.05). Mixed failure mode was the most frequent outcome for both methods. The mixing method employed for AH Plus Jet sealer significantly influences both the physicochemical and mechanical properties of the material. Manual mixing demonstrated better properties compared to auto mix.